2020
DOI: 10.2147/jpr.s236786
|View full text |Cite
|
Sign up to set email alerts
|

<p>Clinical Intervention Using Body Shadows for a Patient with Complex Regional Pain Syndrome Who Reported Severe Pain and Self-Disgust Toward the Affected Site: A Case Report</p>

Abstract: A woman in her thirties developed complex regional pain syndrome in her left shoulder due to a traffic accident. She demonstrated autonomic nervous symptoms (swelling, sweating, and skin color asymmetry) in her left hand, severe allodynia, neglect-like symptoms (NLS), impaired body image associated with impaired body awareness, and functional impairment of the left shoulder and elbow. She also reported physical self-disgust toward her affected limb, describing it as "reptilian," as well as aversion to touching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Six different designs were identified; 14 single case studies, 3649 eight randomised control trials, 5057 eight prospective cohort studies, 5865 four case series, 66–68 three retrospective notes reviews, 6971 and one mixed methods study. 72 13 interventions were categorised as sensory retraining, 37,38,40,42,54,55,57,58,63,64,67,69,71 seven as kinesiotherapy, 36,39,45,48,65,66,68 seven as manual therapies, 43,44,46,49,53,56,73 six as physical modalities, 5052,59,62,72 and five as interdisciplinary treatment. 41,47,60,61,70…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Six different designs were identified; 14 single case studies, 3649 eight randomised control trials, 5057 eight prospective cohort studies, 5865 four case series, 66–68 three retrospective notes reviews, 6971 and one mixed methods study. 72 13 interventions were categorised as sensory retraining, 37,38,40,42,54,55,57,58,63,64,67,69,71 seven as kinesiotherapy, 36,39,45,48,65,66,68 seven as manual therapies, 43,44,46,49,53,56,73 six as physical modalities, 5052,59,62,72 and five as interdisciplinary treatment. 41,47,60,61,70…”
Section: Resultsmentioning
confidence: 99%
“…These included Prism Adaptation, 37,40,54,58 Graded Motor Imagery, 38,57,67 Virtual Reality, 55,64,69 graded somatosensory stimulation, 63,71 and body shadows. 42…”
Section: Discussionmentioning
confidence: 99%
“…Posttraumatic stress [ 8 ], catastrophic thinking [ 9 ], and depression and anxiety [ 10 ] are psychosocial factors reported to affect CRPS pain. Moreover, Hirakawa et al [ 11 ] reported a case of CRPS in which pain was affected by aversion for the appearance of the affected limb. Osumi et al [ 12 ] and Turner-Cobb et al [ 13 ] reported that such aversion for the affected limb can increase pain sensitivity [ 14 ] and exacerbate pain, and McCabe et al [ 15 ] and colleagues [ 13 ] suggested that developing negative feelings regarding the appearance of the affected limb is an important symptom of CRPS.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, in cases where pain is related to negative emotions, such as disgust for the affected limb, symptoms may be temporarily relieved during MT, but when the patient sees the actual affected area, the pain reappears along with disgust, and the symptoms may not show consistent improvement. It has been reported that treatment with body shadow in such cases resulted in continuous improvement of symptoms [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation